The Effects of Academic Incubators on University Innovation - Kolympiris, Christos; Klein, Peter G. (Strategic Entrepreneurship Journal, 2017)
Research summary In this article, we analyze the impact of academic incubators on the quality of innovations produced by U.S. research‐intensive academic institutions. We show that establishing a university‐affiliated incubator is followed by a reduction in the quality of university innovations. The conclusion holds when we control for the endogeneity of the decision to establish an incubator using the presence of incubators at peer institutions as an instrument. We also document a reduction in licensing income following the establishment of an incubator. The results suggest that university incubators compete for resources with technology transfer offices and other campus programs and activities, such that the useful outputs they generate can be partially offset by reductions in innovation elsewhere. Managerial summary Do university incubators drain resources from other university efforts to generate innovations with commercial relevance? Our analysis suggests that they do: after research‐intensive U.S. universities establish incubators, the quality of university innovations, which we measure with patents, drops. This finding has immediate implications for practice, as it suggests that the benefits and costs of incubation should not be analyzed in isolation. Rather, the effects of incubators extend to the overall innovation performance of the university. It follows that measuring the net economic effect of incubators is challenging because besides the effects on innovation efforts, the presence of an incubator may attract particular kinds of faculty and students, enhance the prestige of the university, generate economic multiplier effects, and benefit the community as a whole. Copyright © 2016 Strategic Management Society.